2019
DOI: 10.1111/fwb.13407
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of hypoxia and fish kairomones on several physiological and life history traits of Daphnia

Abstract: 1. Numerous studies have tested the combined effect of the threat of predation by fish and low oxygen concentrations on the phenotypic plasticity of Daphnia.These studies assessed the trade-off between minimising predation risk and the negative effects of oxygen deficiencies in the context of depth selection behaviour. We tested whether this trade-off also affects physiological and life history traits. We expected an interactive effect between the threat of fish predation and low oxygen concentrations, such, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 73 publications
4
18
0
Order By: Relevance
“…Even though there is evidence that prey organisms are able to react differently to some fish species [222], there are contradictory studies that still find no difference in defence induction when Daphnia were exposed to different fish species (e.g., [220,231]). As pointed out in the former sections, the response to fish predators is usually expressed in accordance with a general pattern, i.e., reduced size and increased reproduction (e.g., [203,210,232]). Thus, the reaction norm may depend on kairomone concentration [220,221], which would not only explain the differences in the reaction norm between fish species (bigger fish might produce more kairomone) but also the response differences between small juvenile and fully-grown adult fish [199].…”
Section: Defence-inducing Cuesmentioning
confidence: 88%
See 1 more Smart Citation
“…Even though there is evidence that prey organisms are able to react differently to some fish species [222], there are contradictory studies that still find no difference in defence induction when Daphnia were exposed to different fish species (e.g., [220,231]). As pointed out in the former sections, the response to fish predators is usually expressed in accordance with a general pattern, i.e., reduced size and increased reproduction (e.g., [203,210,232]). Thus, the reaction norm may depend on kairomone concentration [220,221], which would not only explain the differences in the reaction norm between fish species (bigger fish might produce more kairomone) but also the response differences between small juvenile and fully-grown adult fish [199].…”
Section: Defence-inducing Cuesmentioning
confidence: 88%
“…Food availability plays a role in the expression of induced defences in freshwater zooplankton, indicating the existence of allocation costs. They are represented by direct metabolic demands, e.g., due to increased respiration rate [23,203], or direct energy and material costs for forming and maintaining defences, such as morphological structures or increased reproduction (e.g., [99,[194][195][196]). Several studies already reported increasing demands of nutrients with increasing predation risk, or reduced defence expression under nutritional constraints [99,[204][205][206][207][208].…”
Section: Costs For Inducible Defencementioning
confidence: 99%
“…The second explanation concerns the differences in the Daphnia and fish species used in the studies, with medium-bodied D. longispina and rudd in our study, and the larger-bodied Daphnia pulicaria and ide ( Leuciscus idus) in the study of Larsson and Lampert (2011). The latter explanation seems likely in the light of observations from numerous studies indicating a great variability in the vulnerability to hypoxia of different Daphnia (Heisey and Porter, 1977; Sell, 1998; Wilczyński et al ., 2019) and fish (Ekau et al ., 2010) species, with D. pulicaria as particularly resistant (Larsson and Lampert, 2012) and ide as a particularly vulnerable fish species to oxygen deficiencies (Mann, 1996).…”
Section: Discussionmentioning
confidence: 91%
“…Vanderploeg et al ., 2009a), two arguments may suggest that the mortality risk from fish would be greater at a decreased oxygen concentration in the metalimnion. The first argument is that persisting in an environment with a low oxygen concentration has high physiological and in turn demographic costs for zooplankton (Kobayashi and Hoshi, 1984; Hanazato and Dodson, 1995; Larsson and Lampert, 2011; Wilczyński et al ., 2019). This is consistent with the field observations that maximum zooplankton density during the day is usually in the top part of the metalimnion with relatively high oxygen concentration, even when the light intensity allows fish to forage in this layer (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation